Psychometric properties of the Chinese version of the Athletic Identity Measurement Scale Plus: A confirmatory study on Chinese adolescents - Shaoshen Wang; Ying Shuai; Garry Kuan; Najib Majdi Yaacob; Yee Cheng Kueh (PLoS ONE, 2026)
Background Athletic identity plays a crucial role in athletes’ psychological well-being and performance. Although the Athletic Identity Measurement Scale Plus (AIMSP) effectively assesses this construct in Western contexts, its application in diverse cultural settings remains challenging. This study aimed to validate the Chinese version of AIMSP (AIMSP-C) among young basketball players in mainland China. Methods A cross-sectional validation study was conducted with 604 adolescent basketball players (301 males, 303 females; mean age = 15.53 years, SD = 1.42) from secondary schools across Shandong Province, China. Participants completed the 22-item AIMSP-C, which assesses five dimensions of athletic identity using an 11-point Likert scale. The scale underwent rigorous forward-backward translation following standard cross-cultural adaptation procedures. Confirmatory factor analysis (CFA) was performed to examine the structural validity, alongside comprehensive reliability and validity assessments. Results CFA supported a five-factor structure (Social Identity, Exclusivity, Self-Identity, Negative Affectivity, and Positive Affectivity) after minor modifications, demonstrating acceptable fit indices (CFI = 0.959, TLI = 0.952, SRMR = 0.083, RMSEA = 0.091 [90% CI: 0.086, 0.096]). The AIMSP-C exhibited strong internal consistency (composite reliability: 0.974–0.989), convergent validity (AVE > 0.50), discriminant validity, and test-retest reliability (ICC: 0.936–0.989). These psychometric properties surpassed those of the original AIMSP. Conclusion The AIMSP-C demonstrates robust psychometric properties for assessing athletic identity among Chinese youth athletes. This validated instrument provides researchers and practitioners with a reliable tool for understanding athletic identity in the Chinese sporting context, facilitating evidence-based approaches to athlete development and psychological support.